Metodología de implementación de un sistema integrado de gestión de las normas ISO 9001 e ISO 30301 para mejorar el desempeño del sector notarial - Mora Contreras, Rafael (Escuela Colombiana de Ingeniería Julio Garvito, 2018)
In the international context, the implementation of different management systems is of great relevance for many organizations, since it offers them the opportunity to improve their overall performance in response to the great challenges generated by the environment. However, from the literature it is pointed out that there is still a great difficulty for organizations to manage several management systems separately, as well as to carry out the integration of several of them, because in the academic community there is still no consensus on the most effective way to do it. Therefore, an innovative methodology for the implementation of an integrated management system for ISO 9001 and ISO 30301 standards is proposed to improve the performance of the notarial sector, from the analysis of integration models, success cases, failure and abandonment of management systems. The study was carried out in a notary office in the department of Cundinamarca, through the analysis of qualitative and quantitative variables. The qualitative variables are examined with a perception questionnaire, addressed to the staff during the application of the implementation methodology; the results highlight the care of their organizational model; reduction of redundancies and duplicities in the administration of the different management systems; the establishment of effective processes for the creation and control of documents; finally, obtaining objective performance metrics. The quantitative variables after the implementation of the integrated management system, highlight improvements in performance over process times, resources and costs. During the development of the methodology, common elements of the sector are identified to affirm their compatibility with any notary according to Colombian legislation.

En el contexto internacional, la implementación de diferentes sistemas de gestión es de gran relevancia para numerosas organizaciones, puesto que les ofrece la oportunidad de mejorar su desempeño global en respuesta a los grandes desafíos que genera el entorno. Sin embargo, desde la literatura se señala que aún existe una notable dificultad por parte de las organizaciones para administrar múltiples sistemas de gestión por separado, así como llevar a cabo la integración de varios de ellos, dado que en la comunidad académica aún no existe un consenso sobre la forma más efectiva para realizarlo. Por lo anterior, se propone una metodología innovadora de implementación de un sistema integrado de gestión de las normas ISO 9001 e ISO 30301 para mejorar el desempeño del sector notarial, a partir del análisis de modelos de integración, casos de éxito, fracaso y abandono de sistemas de gestión. El estudio se llevó a cabo en una notaría del departamento de Cundinamarca, mediante el análisis de variables cualitativas y cuantitativas. Las variables cualitativas se examinan con un cuestionario de percepción, dirigido al personal durante la aplicación de la metodología de implementación; los resultados destacan el cuidado de su modelo organizacional; reducción de redundancias y duplicidades en la administración de los diferentes sistemas de gestión; el establecimiento de procesos eficaces para la creación y control de documentos; finalmente, la obtención de métricas objetivas de desempeño. Las variables cuantitativas tras la implementación del sistema integrado de gestión, destacan mejoras en el desempeño sobre los tiempos de proceso, recursos y costos. Durante el desarrollo de la metodología, se identifican elementos comunes del sector para afirmar su compatibilidad con cualquier notaría conforme a la legislación colombiana.
Keywords: Sistemas integrados de gestión; NTC ISO 9001; NTC ISO 30301; Integrated management systems; NTC ISO 9001; NTC ISO 30301